2013
DOI: 10.1080/10916466.2011.559507
|View full text |Cite
|
Sign up to set email alerts
|

The Surveying of Soil and Groundwater Pollution in a Petroleum Refinery and the Potential of Bioremediation for Oil Decontamination

Abstract: Soil contamination with crude oil is an important worldwide issue and the remediation of oil contaminated soils, sediments and groundwater is a major environmental challenge. In the target area of this survey, which is a petroleum refinery near Tehran, soil and groundwater pollution, and its source, contaminated area, and distribution of pollution were studied by means of different measurements. Oil content and volatile organic compounds were measured to determine soil and groundwater contamination. The invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As conventional cleanup strategies are being used to remove the heavy metal ions from the polluted areas but these are expensive and feasible only in small areas. Researchers have found new cost effective methods that include the use of microorganisms (Naureen and Rehman 2016;Sher et al 2020b), biomass (Jaafari and Yaghmaeian 2019;Sultana et al 2020) and live plants (Zargar et al 2013;Ojuederie and Babalola 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As conventional cleanup strategies are being used to remove the heavy metal ions from the polluted areas but these are expensive and feasible only in small areas. Researchers have found new cost effective methods that include the use of microorganisms (Naureen and Rehman 2016;Sher et al 2020b), biomass (Jaafari and Yaghmaeian 2019;Sultana et al 2020) and live plants (Zargar et al 2013;Ojuederie and Babalola 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Petroleum releases to the environment occur across the extraction (Fisher & Sublette, ; Nigerian Federal Ministry of Environment [FME], ), refining (Pasadakis, Gidarakos, Kanellopoulou, & Spanoudakis, ; Schneider et al., ; Zargar, Sarrafzadeh, Taheri, & Tavakoli, ), and storage (Arnold, Parfitt, & Kaltreider, ; Biesterveld, Scheiter, & Marsh, ; Kehew & Lynch, ) phases of resource use. Released hydrocarbons in the terrestrial subsurface tend to be spread across multiple phases, including as sorbed chemicals to soil organic matter, as dissolved components within groundwater, as gases within vadose zone pore spaces, and as light nonaqueous phase liquid (LNAPL) across the soil column and particularly near the water table (Newell, Acree, Ross, & Huling, ).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that these industrial emissions were accidently and carelessly discharged into the lakes, rivers, and oceans, resulting in the formation of a large area of oil pollution throughout the world. [8][9][10][11] This oil pollution not only causes tremendous hazard to the natural environment that humans closely depend on, but also undermines the sustainable development of the ecological environment. Quantitative analysis of liquid oil pollutants is essential for tracing the source of pollutant elements and crucial to the subsequent promulgation and implementation of reasonable prevention and governance measures.…”
mentioning
confidence: 99%